(3HMhK aj GdEbJUGO GdESdGej hfXGeg GdeGdi (B/s - (3GdcaQGfj, Yha eMehOs ((3GdEScfOQjI(B: s (3eDSSI GdKbGaI GdLGeYjI(B, s, 2007)
(3jVe GdeQJcRGJ GdCSGSjI ddGbJUGO GdGSdGej, GdadSaI GdGbJUGOjI ddfXGe GdeGdj aj GdGbJUGO GdeGdj, GdNUGFU GdeejRI ddfXGe GdeGdj GdGSdGej GdJj JejRg Yf GdfXGe GdeGdj GdehVYj, GdBKGQ GdGbJUGOjI hGdGLJeGYjI ddGfaGb GdYGe aj GdGSdGe, OQGSI aj GdVQGFH GdeHGTQI hGdVQGFH ZjQ GdeHGTQI aj GdfXe GdeGdjI GdeYGUQI haj GdfXGe GdeGdj GdGSdGej, eGdjI GdOhdI GdGSdGejI aj acQ GHf JejeI, GdMQH aj GdGSdGe VhGHWgG hBKGQgG GdGbJUGOjI, GUOGQ GdfbhO hGdeMGaXI YdjgG aj GdOhdI GdGSdGejI, OhQ GdHfhc GdGSdGejI aj GdJfejI GdGbJUGOjI, GdQbGHI GdeGdjI aj GdeUGQa hHjhJ GdeGd GdGSdGejI GdSjGSI GdeGdjI hGdfbOjI OQGSI JMdjdjI aj GdacQ GdZQHj hGdGSdGej, GdQbGHI Ydi GdeGd GdYGe aj GdacQ GdGSdGej, GdGfaGb GdGSJKeGQj aj GdOhdI GdGSdGejI aj acQ GdbGVj GHj jhSa, GdJMOj GdGbJUGOj OQGSI JMdjdjI ddGbJUGO GdYGe dOhd GdNdjL GdYQHj GdGSdGejIs
(3HHdjhZQGajG(B: (3U(B.586-587s
Keywords: (3GdGbJUGO GdGSdGejs; (3GdHfhc GdGSdGejIs; (3GdfXGe GdfbOjs